Bridging the Divide: Digital Innovation as a Catalyst for Healthcare Equity between Urban and Rural Populations - Pawar, Hemant (International Journal of Computing and Engineering, 2025)
Healthcare disparities between rural and urban populations represent a persistent challenge in modern healthcare systems, with rural residents experiencing reduced access to preventive services, specialty care, and medications. These disparities manifest in higher rates of avoidable hospitalizations, longer travel times for specialty care, and lower medication adherence. Digital health innovations offer promising solutions to bridge this divide through the strategic implementation of telehealth platforms, electronic prescribing systems, and artificial intelligence tools. This article examines the impact of comprehensive digital health implementation on rural healthcare access and outcomes. Findings demonstrate that telehealth expansion substantially reduced travel burdens and improved appointment completion rates among rural populations. Electronic prescribing systems addressed medication access challenges in pharmacy deserts, while AI-powered clinical decision support extended specialist-level care to underserved communities. However, technology alone proved insufficient—successful implementation required supportive policy frameworks, infrastructure development, and community engagement strategies. The integration of these elements created a sustainable ecosystem that significantly reduced rural-urban healthcare disparities while maintaining quality standards across geographic boundaries.